2020
DOI: 10.3390/sym12030485
|View full text |Cite
|
Sign up to set email alerts
|

Finite Difference Approximation Method for a Space Fractional Convection–Diffusion Equation with Variable Coefficients

Abstract: Space non-integer order convection–diffusion descriptions are generalized form of integer order convection–diffusion problems expressing super diffusive and convective transport processes. In this article, we propose finite difference approximation for space fractional convection–diffusion model having space variable coefficients on the given bounded domain over time and space. It is shown that the Crank–Nicolson difference scheme based on the right shifted Grünwald–Letnikov difference formula is unconditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…An improved matrix transform numerical method is proposed in Reference [23] to solve one dimensional space fractional advection-dispersion model and its analytical solution is found using padé approximation. Recently, space fractional convection-diffusion with variable coefficients are solved using shifted Grünwald-Letnikov difference operator for space and Crank-Nicolson scheme for time that produce second order convergence both in time and space with extrapolation was studied [24].…”
Section: Introductionmentioning
confidence: 99%
“…An improved matrix transform numerical method is proposed in Reference [23] to solve one dimensional space fractional advection-dispersion model and its analytical solution is found using padé approximation. Recently, space fractional convection-diffusion with variable coefficients are solved using shifted Grünwald-Letnikov difference operator for space and Crank-Nicolson scheme for time that produce second order convergence both in time and space with extrapolation was studied [24].…”
Section: Introductionmentioning
confidence: 99%
“…tion (9) for different values of time t, then for the various nodes we have discretized equations. These simultaneous linear equations are evaluated in MATLAB [20] using the successive-over relaxation (SOR) method, and then temperature profile values for all nodes (x) are represented in Table 3.…”
Section: Fully Implicit Hybrid Scheme Numerical Resultsmentioning
confidence: 99%
“…Such an equation has an analytic solution are only possible for a restricted and limited number of cases [7]. Due to this, several numerical techniques have been developed for the numerical approximations of convection-diffusion problems [8,9]. The finite difference approximation method, the finite element method, as well as finite volume techniques are most widely used for computational fluid dynamics (CFD) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Equations (32) and (33) are solved using the one-dimensional Thomas' algorithm and are given the following form…”
Section: Numerical Solution Of the Problemmentioning
confidence: 99%
“…In [32], finite-difference approximation was proposed for the space fractional convective-diffusion model, which has the coefficients of space variable on the given bounded domain over time and space. It was shown that the Crank-Nicolson difference scheme based on the right shifted Grünwald-Letnikov difference formula is unconditionally stable and also has second-order consistency both in temporal and spatial terms with extrapolation to the limit approach.…”
Section: Introductionmentioning
confidence: 99%